Ikan Badut dan Anemon Laut sebagai Ide Penciptaan Karya Batik Lukis untuk Hiasan Ruang Anak - Aqsya, Jihan Yufatika; Jupriani, Jupriani (YASIN, 2025)
Indonesia's rich marine biodiversity, including the symbiotic relationship between clownfish and sea anemones, has not been widely raised as a theme in contemporary batik works, even though it has the potential to become a medium for children's education. This research aims to create a batik painting with the theme of clownfish and sea anemone for children's room decoration, which combines aesthetic values and educational messages about the importance of protecting marine ecosystems. The method used is practice-based research through five stages: preparation, elaboration, synthesis, concept realization, and completion. Data was collected through visual observation, literature study, consultation with batik artisans and art observers, and evaluation of works through exhibitions. The technique applied is painted batik with color colet using a brush on primissima mori cloth, plus decorative elements in the form of glitter. The research results are ten painted batik works that represent the theme of underwater life, with the application of fine art principles such as unity, balance, and rhythm, as well as presenting cheerful and educational visuals for children. In conclusion, these painted batik works not only successfully display the beauty of the relationship between clownfish and sea anemone, but also effectively become a medium to raise children's awareness of the importance of marine biodiversity conservation.